2013
DOI: 10.1186/1475-2875-12-415
|View full text |Cite
|
Sign up to set email alerts
|

Trends in chloroquine resistance marker, Pfcrt-K76T mutation ten years after chloroquine withdrawal in Tanzania

Abstract: BackgroundPlasmodium falciparum resistance to anti-malarial drugs remains a major obstacle to the control of malaria. In 2001 Tanzania replaced chloroquine (CQ) with sulphadoxine-pyrimethamine (SP) as first-line drug, which in turn was replaced by artemisinin combination therapy in 2006. SP has however, continued to be used in intermittent preventive treatment of malaria in pregnancy (IPTp) despite reports of high levels of resistance to SP due to the lack of alternatives to SP for IPTp. Recent reports have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
64
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 41 publications
13
64
1
Order By: Relevance
“…In South America, the prevalence of the CQR marker K76T in the drug efflux transmembrane protein PfCRT has remained high, despite CQ having been abandoned for the treatment of P. falciparum infections (7)(8)(9). This situation contrasts with multiple settings in Africa, where the majority of molecular studies (10)(11)(12)(13) have documented an increase in the prevalence of WT pfcrt after CQ withdrawal. An analysis of the diversity of microsatellites flanking pfcrt in Malawi showed that the return to CQ susceptibility was caused by a reexpansion of the WT PfCRT haplotype (11).…”
mentioning
confidence: 56%
“…In South America, the prevalence of the CQR marker K76T in the drug efflux transmembrane protein PfCRT has remained high, despite CQ having been abandoned for the treatment of P. falciparum infections (7)(8)(9). This situation contrasts with multiple settings in Africa, where the majority of molecular studies (10)(11)(12)(13) have documented an increase in the prevalence of WT pfcrt after CQ withdrawal. An analysis of the diversity of microsatellites flanking pfcrt in Malawi showed that the return to CQ susceptibility was caused by a reexpansion of the WT PfCRT haplotype (11).…”
mentioning
confidence: 56%
“…These two studies included parasites from all patients and not a special group of patients with sickle cell disease. Similarly, higher prevalence of these mutants at pfcrt have been reported recently from elsewhere Tanzania (Ngasala et al, 2011;Malmberg et al, 2013;Mohamed et al, 2013). However, in these other Tanzanian studies the prevalence of patients with SCD was not stated.…”
Section: Discussionmentioning
confidence: 72%
“…After discontinuation of CQ use, several studies in African countries have reported different prevalence of pfcrt K76T mutation. In some countries there is clear re-emergence of wild type strains coupled with CQ sensitivity (Kublin et al, 2003;Lauffer et al, 2006;Ginsburg et al, 2006;Frosch et al, 2011;Kamugisha et al, 2012;Mohamed et al, 2013;Malmberg et al, 2013). In other countries the level of CQ resistance is going down very slowly or is fixed (Frosch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other factors such as the variation in the intensity of malaria transmission in different geographical locations coupled with the introduction of closely related antimalarial agents such as amodiaquine may further explain the observed variation. 42 The current study provides evidence of a slow progressive decline in the prevalence of genotypic (Pfcr K76T and Pfmdr N86Y) CQ resistance among P. falciparum parasites in Uganda. This is indicative of the persistent possibility of unfavorable clinical outcomes if CQ is introduced in malaria treatment in the country.…”
Section: Discussionmentioning
confidence: 98%
“…In Ghana, for example, the prevalence of Pfcrt T76 declined from 80% to ∼60% between 2005 and 2011. 41 A study by Mohammed et al 42 in Tanzania found a CQ susceptibility rate of more than 90% among P. falciparum parasite isolates following 12 years after the change in policy. In Kenya, when CQ use in malaria treatment was stopped from 1993 to 2006, CQ susceptibility rose from 5% to 40%.…”
Section: Discussionmentioning
confidence: 99%